Whistle Blowing Systems Effectiveness, Behavioral Insight for Curbing Bureaucratic Corruption. FOI Act Implement Gaps - Benjamin Erhirhie (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study explores the critical drivers of anti-corruption effectiveness by examining the nexus between whistleblowing systems (WBS) performance, behavioral triggers in bureaucratic corruption and implementation gaps in the freedom of information (FOI) Act. Utilizing a Multi theoretical framework – institutional Theory, the theory of planned behavior (TPB) and protection motivation Theory (PMT) - the research analyzes why formal transparency laws often fail to produce substantive accountability. Institutional Theory reveals a “decoupling” effect, where public agencies adopt anti-corruption frameworks for legitimacy while maintaining a culture of secrecy. Behavioral insights, grounded in TPB, suggest that, whistleblowing intentions are hindered by negative subjective norms and a low sense of behavioral control among public servant. Furthermore, PMT highlights that, the fear of retaliation often outweighs the motivation to report wrong doing rendering many WBS ineffective. The study identifies significant implementation gaps in the FOI Act, specifically the conflict with the official secrets Act, lack of budgetary support for digitalization and the absence of punitive sanctions for non-compliance. Findings indicate that, for whistleblowing and FOI systems to succeed, policy must shift from purely structural requirements to behavioral interventions that lower the perceived risk of reporting and normalize transparency. The research concludes with recommendations for enacting comprehensive whistleblower protection legislation, automating proactive disclosures under the FOI Act and utilizing behavioral nudges to foster and institutional culture of integrity. These insights provide a road map for policy makers to bridge the gap between law on paper and “law in practice” within the public sector.